2018
DOI: 10.1186/s12937-018-0366-6
|View full text |Cite
|
Sign up to set email alerts
|

User-documented food consumption data from publicly available apps: an analysis of opportunities and challenges for nutrition research

Abstract: BackgroundThe need for a better understanding of food consumption behaviour within its behavioural context has sparked the interest of nutrition researchers for user-documented food consumption data collected outside the research context using publicly available nutrition apps. The study aims to characterize the scientific, technical, legal and ethical features of this data in order to identify the opportunities and challenges associated with using this data for nutrition research.MethodA search for apps colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 43 publications
(54 reference statements)
0
27
0
1
Order By: Relevance
“…On a more detailed level, Table 6 includes the categories and subcategories of evaluation artefacts and the numbers of papers that covered them. Healthcare expert evaluation [69], user evaluation [21], [72] [2], [6], [8], [17], [21], [22], [24], [27], [41], [68]- [70], [72], [75], [77]- [79], [81]- [83] Privacy policy (PP) and Terms of Agreement (ToA) content evaluation Readability assessment [17], [23], [56], [116] [1], [6], [17], [22]- [24], [41], [55], [56], [58], [60], [68], [71], [74], [75], [77], [78], [83], [116] Technical security mechanisms evaluation…”
Section: ) Evaluation Objectives and Artefactsmentioning
confidence: 99%
“…On a more detailed level, Table 6 includes the categories and subcategories of evaluation artefacts and the numbers of papers that covered them. Healthcare expert evaluation [69], user evaluation [21], [72] [2], [6], [8], [17], [21], [22], [24], [27], [41], [68]- [70], [72], [75], [77]- [79], [81]- [83] Privacy policy (PP) and Terms of Agreement (ToA) content evaluation Readability assessment [17], [23], [56], [116] [1], [6], [17], [22]- [24], [41], [55], [56], [58], [60], [68], [71], [74], [75], [77], [78], [83], [116] Technical security mechanisms evaluation…”
Section: ) Evaluation Objectives and Artefactsmentioning
confidence: 99%
“…UK compilers work with their international counterparts to produce harmonised, standardised data, and these initiatives often start as research projects, such as the EuroFIR Network of Excellence under EU FP6 (Westenbrink et al 2016). New research initiatives such as the Food, Nutrition and Health Research Infrastructure, developed from the outcomes of the RICHFIELDS project (Maringer et al 2018), and large‐scale projects such as the Food and Nutrition Security Cloud Horizon2020 project (http://www.fns-cloud.eu/) are reshaping how food and nutrition data are stored, shared and utilised across Europe. Food composition data will form an integral part of any future over‐arching research infrastructure or federation of food data.…”
Section: Who Uses Food Composition Data?mentioning
confidence: 99%
“…Furthermore, food consumption information could be considered personal data. Therefore, this would present a challenge in Europe, given that General Data Protection Regulation (GDPR) would apply 38 . Another study related to commercial pig farming found that analysing secondary data was a challenge since there were limitations related to the combined use of several data sources.…”
Section: Technical Challenges Of Reusingmentioning
confidence: 99%